Efficacy of free glutathione and niosomal glutathione in the treatment of acetaminophen-induced hepatotoxicity in cats - Denzoin Vulcano, L. A. (2013)
Acetaminophen (APAP) administration results in hepatotoxicity and hematotoxicity in cats. The response to three different treatments against APAP poisoning was evaluated. Free glutathione (GSH) (200mg/kg), niosomal GSH (14 mg/kg) and free amino acids (180 mg/kg of N-acetylcysteine and 280 mg/kg of methionine) were administered to cats that were intoxicated with APAP (a single dose of 150 mg/kg, p.o.). Serum concentration of alanine aminotransferase (ALT) along with serum, liver and erythrocyte concentration of GSH and methemoglobin percentage were measured before and 4, 24 and 72 hours after APAP administration. Free GSH (200 mg/kg) and niosomal GSH (14 mg/kg) were effective in reducing hepatotoxicity and hematotoxicity in cats intoxicated with a dose of 150 mg/kg APAP. We conclude that both types of treatments can protect the liver and haemoglobin against oxidative stress in APAP intoxicated cats. Furthermore, our results showed that treatment with niosomal GSH represents an effective therapeutic approach for APAP poisoning.